Effect of the cosmological transition to metal-enriched star formation on the hydrogen 21-cm signal. Issue 3 (16th June 2022) - Magg, Mattis; Reis, Itamar; Fialkov, Anastasia; Barkana, Rennan; Klessen, Ralf S; Glover, Simon C O; Chen, Li-Hsin; Hartwig, Tilman; Schauer, Anna T P
ABSTRACT: Mapping cosmic dawn with 21-cm tomography offers an exciting new window into the era of primordial star formation. However, self-consistent implementation of both the process of star formation and the related 21-cm signal is challenging, due to the multiscale nature of the problem. In this study, we develop a flexible semi-analytical model to follow the formation of the first stars and the process of gradual transition from primordial to metal-enriched star formation. For this transition, we use different scenarios with varying time-delays (or recovery times) between the first supernovae and the formation of the second generation of stars. We use recovery times between 10 and 100 Myr and find that these delays have a strong impact on the redshift at which the transition to metal-enriched star formation occurs. We then explore the effect of this transition on the 21-cm signal and find that the recovery time has a distinctive imprint in the signal. Together with an improved understanding of how this time-delay relates to the properties of Population III stars, future 21-cm observations can give independent constraints on the earliest epoch of star formation. As the transition away from the primordial star formation is expected to occur at high redshifts, here we ignore the impact of X-ray and ionizing radiation, focusing on the effect of Ly α photons on the 21-cm signal.